"Everyone Needs a Breath of Fresh Air": Workplace Impact on Nurses' Smoking Behaviors. Issue 4 (July 2020) - Petersen, Anne Berit; Sarna, Linda; Rezk-Hanna, Mary; Wells, Marjorie; Nohavova, Iveta; Bialous, Stella
Abstract : Background: Europe continues to have among the highest worldwide prevalence of adult smoking (28%) and the highest among females (19%). Nurses' rates of smoking in the region are comparable or higher than the general female population. Nurses who smoke are less likely to intervene with patients who smoke; therefore, supporting nurses' efforts to quit is critical to promoting nurses' well-being and strengthening the profession's impact on prevention of tobacco-induced diseases. Objective: The aim of this study was to explore nurses' perceptions of hospital workplace factors that influence nurses' smoking and quitting behaviors in Central and Eastern Europe. Methods: Each country had a project director involved in the recruitment of participants and the translation of instruments. Using a moderator guide, focus groups (N = 9) about smoking and quitting were conducted in 5 countries (Czech Republic, Hungary, Romania, Slovakia, Slovenia) among 82 nurses who self-reported as current or former smokers. Recorded transcripts were translated and analyzed using content analysis methods. Results: The majority of nurses were female (94%) and currently smoking (65%). Four major themes were identified that describe workplace factors influencing nurses' smoking behaviors and efforts to quit: (1) taking breaks, (2) effect of smoking on patient interactions, (3) perceived collegial support for quitting, and (4) impact of workplace policies. Conclusions: Workplace factors influence nurses smoking and quitting behaviors. Implications for Practice: Changes in healthcare systems and policies are needed to support nurses' quit efforts. Additional education is needed to ensure that nurses understand issues related to smoking and interactions with patients.